ANALISIS PENGGUNAAN GAYA BAHASA PERBANDINGAN KUMPULAN PUISI PERJAMUAN RINDU KARYA DIANA PUTERI ZAHRO - Rofiq, Asngadi (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the types of language use and educational values ??contained in the poetry collection "Perjamuan Rindu" by Diana Puteri Zahro which will be published in 2021. This study used descriptive qualitative method. The data source in this research is a collection of poems contained in the poem Perjamuan Rindu by Diana Puteri Zahro. Data collection techniques in research use content analysis (Text) techniques. In qualitative research, content analysis or content analysis is used. The results of this study indicate that the use of comparative figurative language in the poetry collection "Perjamuan Rindu" by Diana Puteri Zahro has types of figurative language: personification, parable/simile, metaphor, allegory. From the language style data there are 21 pieces of data. In the Personification language style there are 5 data, Parable/Simile there are 2 data, Metaphor there are 8 data, Allegory there are 6 data.